2017
DOI: 10.1093/mnras/stx747
|View full text |Cite
|
Sign up to set email alerts
|

Very hard states in neutron star low-mass X-ray binaries

Abstract: We report on unusually very hard spectral states in three confirmed neutron-star low-mass X-ray binaries (1RXS J180408.9−342058, EXO 1745−248, and IGR J18245−2452) at a luminosity between ∼ 10 36−37 erg s −1. When fitting the Swift X-ray spectra (0.5 -10 keV) in those states with an absorbed power-law model, we found photon indices of Γ ∼ 1, significantly lower than the Γ = 1.5 -2.0 typically seen when such systems are in their so called hard state. For individual sources very hard spectra were already previou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 38 publications
6
56
0
Order By: Relevance
“…The photon index versus the 0.5-10 keV X-ray luminosity for our five sources. For 1RXS J180408.9-342058, EXO 1745-248, and IGR J18245-2452 we show the same data as presented in Parikh et al (2017, their Figure 1). In addition we have now included IGR J00291+5934 and Swift J0911.9-6452 for the first time.…”
Section: Connection With Amxpssupporting
confidence: 74%
See 2 more Smart Citations
“…The photon index versus the 0.5-10 keV X-ray luminosity for our five sources. For 1RXS J180408.9-342058, EXO 1745-248, and IGR J18245-2452 we show the same data as presented in Parikh et al (2017, their Figure 1). In addition we have now included IGR J00291+5934 and Swift J0911.9-6452 for the first time.…”
Section: Connection With Amxpssupporting
confidence: 74%
“…Both stay in a quasi-stable state for 1 to 2 months at a luminosity between 10 36 and 10 37 erg s −1 before they exhibited the brightest part of their outbursts (where the outburst luminosity peaked around a factor 10 higher; i.e., the transition into the soft, banana branch state). During this quasi-stable state the spectra for both sources were very hard (as measured in the 0.5-10 keV range) with photon indices between 1 and 1.5 (see also Parikh et al 2017). In addition, for both sources we found that they exhibited very strong variability over a large range of frequencies (see Figure 4, left panel).…”
Section: A Distinct Spectral-timing State In 1rxsmentioning
confidence: 94%
See 1 more Smart Citation
“…The X-ray spectrum in the range of 0.5 − 10 keV for lowlevel accreting NSs can generally be well fitted with the model with two components, i.e., a thermal soft X-ray component plus a power-law component (e.g. Jonker et al 2004b;Campana et al 2008a,b;Fridriksson et al 2010Fridriksson et al , 2011Armas Padilla et al 2013a;Degenaar et al 2013;Campana et al 2014;Parikh et al 2017;Vats et al 2018). For certain low-level accreting NSs, the temperature of the soft X-ray component decreases with decreasing the X-ray luminosity during the decay after the outburst (Armas Padilla et al 2013b;Degenaar et al 2013;Bahramian et al 2014).…”
Section: Introductionmentioning
confidence: 88%
“…The origin of this shallow heat source is unknown and is important to resolve because the cooling curve can be used to constrain a number of different aspects of crust physics (such as conductivity of the crust and pasta, and the core specific heat; Brown & Cumming 2009;Horowitz et al 2015;Cumming et al 2017). Most systems need ∼1-2 MeV nucleon −1 of shallow heating to explain their cooling curves (e.g., Degenaar et al 2014;Parikh et al 2017;Wijnands et al 2017). The transient NS LMXB MAXI J0556−332 (hereafter J0556) was discovered on 2011 January 11 (Matsumura et al 2011) and exhibited a ∼16 month outburst.…”
Section: Introductionmentioning
confidence: 99%